PENERAPAN METODE INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI BUMI DAN ALAM SEMESTA SISWA KELAS V SEKOLAH DASAR - Mahlianurrahman Mahlianurrahman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This study aims to increase critical thinking skills of students with inquiry methods and to describe the implementation of an inquiry methods on science competence. This research is classroom action research, which consisted of three cycles. This study was conducted in Elementary School Pasi Pinang academic year 2017/2018. The objects were all students of class V consisting of 24 students.The data were collected using tests, The results show that the implementation of the inquiry methods can improve students' critical thinking skills in science competencies.Keywords: Critical thinking skills, method inquiry